Effect of hydrogen peroxide and its combination with nano-hydroxyapatite or nano-bioactive glass on the enamel demineralization and tooth color: An in vitro study - Elham Kheradmand; Alirea Daneshkazemi; Abdolrahim Davari; Maede Kave; Solmaz Ghanbarnejad (Wolters Kluwer Medknow Publications, 2023)
Background: Patient demand for esthetic dental treatments is increasing, and among different techniques, tooth bleaching is a popular procedure for smile improvement. There is a controversy over the demineralizing effect of hydrogen peroxide (HP) containing bleaching agents on tooth enamel. The aim of this study was to evaluate the effect of HP and its combinations with hydroxyapatite (HA) and bioactive glass (BG) on enamel demineralization and tooth color changes. Materials and Methods: Three groups of 20 teeth were used. Bleaching regimens included HP alone, HP + HA, and HP + BG. Bleaching was repeated at six periods of 15 min. Energy dispersive spectrometry was performed to evaluate calcium, phosphorus, sodium, magnesium, and fluoride content of superficial enamel before and after bleaching. Tooth color was evaluated by spectrophotometer before and after bleaching and ΔE values were calculated. Data were statistically analyzed using SPSS version 17. Results: Ca and P content was increased significantly in group HP + BG (P < 0.05). There was no significant difference in ΔE values between the three groups (P > 0.05).(p value = 0.34). Conclusion: Addition of BG to HP can increase superficial enamel mineral content after bleaching and has no effect on tooth color changes in comparison to HP alone.